Prospects for a potential African gas renaissance en route to a "just energy transition" - Mostefa A. Ouki (The Oxford Institute for Energy Studies, 2023)
The impact of the Russia-Ukraine war on the natural gas trade, inter alia, continues to be felt well beyond Europe's borders. As the accelerated decarbonisation of the world's economies is being pushed forward, Europe's unexpected interest in alternative sources of gas imports to replace Russian gas has triggered a temporary wave of political enthusiasm for African gas. In Africa, where attracting investments in hydrocarbon projects was complicated even before the rise of investment restrictions due to new international decarbonisation measures, such European interest in gas has been given a cautious welcome. But it also provides another opportunity for African policymakers to reiterate their deep frustration about the restricted flows of international hydrocarbon investments in Africa. Faced with uncertain investment prospects in the energy sector which would address Africa's persistent low level of energy access, African countries are attempting to leverage the present interest in African gas to fully monetise their natural gas resources or reserves. The potential emergence of a new global 'golden age' for natural gas was explored a couple of times during the last decade, but regions like Africa have yet to experience it. Could the fallout of the Russia-Ukraine war and its impact on international gas markets bring about the start of a structural change in Africa's natural gas scene? This paper focuses on two key questions: will the natural gas crisis in Europe serve as a catalyst for wider gas developments in Africa, and what are the implications for the continent's 'just energy transition'?
Keywords: 330; Africa; energy; Energy Transition; Gas; Natural gas